The Internalization of Tabayyun Values in the Merdeka Curriculum: A Study of the PAI Subject at Pertiwi 2 Padang High School - Ilman, Mhd Zidni; Kanus, Oktari (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
The development of digital technology has increased the flow of information, which is not always verified, requiring students to adopt a critical and cautious attitude towards information. From the perspective of Islamic education, the value of tabayyun (verification) becomes an important principle in fostering critical, objective, and responsible attitudes. This study aims to analyze the process of internalizing the value of tabayyun in Islamic Religious Education (PAI) learning based on the Merdeka Curriculum, the strategies employed by PAI teachers to instill it, and the supporting and inhibiting factors. This research uses a qualitative approach with a case study method at Pertiwi 2 Padang High School. Data were collected through interviews, observations, and documentation, then analyzed through data reduction, data presentation, and conclusion drawing, using triangulation. The results show that the internalization of tabayyun values occurs through stages of value transformation, value transaction, and value transinternalization, which are implicitly integrated into critical thinking learning. Supporting factors include school policies that support character education, a conducive religious environment, and adequate digital facilities, while inhibiting factors include students' low interest in social issues, limited learning time, and uneven teacher understanding of the Merdeka Curriculum.